The effect of salience of social identity and university intergroup situation on individual-group orientation amongst minority students in South Africa - Jean, Benjamin (Department of Psychology, 2026)
The social identity: theor'y,' of intergroup relations (Tajfel and Turner 1979) was examined, in the form of a field study, in terms of the extent to which it can account for the observation that incidents of group behaviour in the form of unrest, boycotting of lectures, and rioting have occurred more frequently among minority students at universities created originally as separate universities for these minority groups, and those attending universities where a limited number of minority students are integrated with the dominant group. Students from the University of the Western Cape (UWC) and from the 1Jniversity of Cape Town (UCT) took part. UWC was originally created as a separate university for 'Coloureds', and the majority of its students are from this minority group. UCT accepts members from this group on a limited basis, while the majority of its students are 1 members of the dominant group. The target group was limited to English-speaking B.A. and B.Corrm. students, born and schooled in the CapeA questionnaire was administered to measure the following variables: (i) the demographic variables of language, hometown, school attended, course and year of study, sex.,age, and parent's occupation?, (ii) salience of social identity: subjects were divided into high and low salience groups on the basis on the basis of their responses on the Twenty Statements test (Kuhn and McPartland 1954); (iii) individual-group orientation: a s~point Llkert-type scale' measuring the extent to which subjects believed that self-fulfilment was attainable by either individual or group means · J (iv) rating of own education - a 10-point scale. The demographic variables of sex, age, year of study and parent's oc.cupation were examined in terms of their relation with salience of social identity and university intergroup situation. The effects of salience of social identity and university intergroup situation 2 on individual-group orientation were examined by means of a two-factorial design. No significant relations emerged between the demographic variables and salience of social identity and university intergroup situation. A significant difference at the 5% level was found between high and low salience of social identity groups - high salience leading to relatively high group orientation. No significant effect of university b.1tergroup situation on individual group orientation was found. No significant differences were found between salience or university groups, on rating of own education. An interaction effect, significant at the 10% level, indicated that the UCT high salience group rated their education higher than the UCT low salience group, while the UWC high salience group rated their education lower than the UWC low salience group. ) The findings are interpreted as supportive evidence for the postulate that: increased group orientation is motivated by social identity - social comparison processes. It is concluded that social identity theory offers a plausible account of the processes vmich cause a shift from individual to group orientated behaviour amongst the minority students in the present sample.